Pengukuran Waktu Kerja untuk Menentukan Jumlah Tenaga Kerja Optimal pada Pembuatan Neon Box: Studi Kasus: CV. Wibisono Kreatif Media - Yunizar Arfiansyah, Muhammad; Herlina, Herlina; Yuwono, Istantyo (Fakultas Teknik UMRI, 2025)
CV Wibisono Kreatif Media is a company engaged in the advertising industry (media advertising), construction, and general printing. CV. Wibisono Kreatif Media produces various products, ranging from neon boxes, flexible neon, embossed letters, sign boards, pylon totems, banner printing, sticker printing, and many more. CV Wibisono Kreatif Media also serves shipping and installation to all regions in Indonesia. The problem that arose was the production of CV Wibisono Kreatif Media neon boxes that did not meet the production target. Using the Time Study and Workload Analysis approach, the results showed the need for an efficient number of workers, which is only 5 workers; there will be 1 worker for the cutting operator, the number of workers for the lamp installation operator decreased from 2 to 1, the assembly operator for the neon box also reduced from 2 workers to 1 worker, then the framework making operator decreased from 2 workers to 1 worker, and finally, the sticker installation and finishing operator remains at 1 worker.